2014
DOI: 10.1002/chem.201403317
|View full text |Cite
|
Sign up to set email alerts
|

Halotriazolium Axle Functionalised [2]Rotaxanes for Anion Recognition: Investigating the Effects of Halogen‐Bond Donor and Preorganisation

Abstract: The anion-templated synthesis of three novel halogen-bonding 5-halo-1,2,3-triazolium axle containing [2]rotaxanes is described, and the effects of altering the nature of the halogen-bond donor atom together with the degree of inter-component preorganisation on the anion-recognition properties of the interlocked host investigated. The ability of the bromotriazolium motif to direct the halide-anion-templated assembly of interpenetrated [2]pseudorotaxanes was studied initially; bromide was found to be the most ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 68 publications
1
38
0
Order By: Relevance
“…Anion-Templated XB Syntheses of Rotaxanes 7·Br and 9·Br 374,375 Figure 104. An anion-templated XB catenane 10·Br·PF 6.…”
Section: Anion Recognition and Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…Anion-Templated XB Syntheses of Rotaxanes 7·Br and 9·Br 374,375 Figure 104. An anion-templated XB catenane 10·Br·PF 6.…”
Section: Anion Recognition and Sensingmentioning
confidence: 99%
“…More recently, the Beer group extended this halogen-bond-mediated anion-templation methodology with 8·Br to prepare a bromotriazolium-containing rotaxane 9·Br (Scheme 3). 375 An RCM reaction of equimolar amounts of the Br − and PF 6 − salts of a bromoimidazolium bisvinyl-appended macrocycle precursor facilitated the synthesis of the all-XB anion-templated catenane 10·Br·PF 6 ( Figure 104). 376 The necessity of the XB interaction between the macrocycle precursor components and the bromide anion for catenane formation was demonstrated when the reaction was repeated in the absence of the halide coordinating anion and only the corresponding ring-closed macrocycle was formed.…”
Section: Halogen-bond-templated Self-assemblymentioning
confidence: 99%
“…[45,48] Further structural insights on XB [3]rotaxane assembly with NO 3 À and Cl À anions were obtained through molecular dynamics (MD) simulations carried out at the atomic level using the GAFF [57,58] within the AMBER14 suite, [59] using GPU cards. [60][61][62] Ther emaining computational details are given in the SI.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Of the relatively few examples of XB anion receptors reported to date,i ti sn oteworthy that all display promising,a nd significantly contrasting, anion recognition behaviour when compared to HB analogues,byvirtue of their comparable bond strengths and more strict linear geometry preference. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] Importantly in as ignificant step forward for highlighting the potential importance of halogen bonding in anion supramolecular chemistry,w eh ave recently demonstrated the first examples of solution phase halogen bonding being exploited to control and facilitate the anion-templated assembly of interlocked structures [43][44][45][46][47] and demonstrated that the incorporation of halogen bond donor atoms into a[ 2]rotaxane host cavity dramatically improves the anion recognition capabilities of the XB interlocked receptor. [48][49][50][51] Herein, we report the synthesis of the first halogen bonding [3]rotaxane host system, containing ab is-iodo triazolium-bis-naphthalene diimide four station axle component, which employs multiple cooperative XB and HB interactions to exhibit enhanced recognition of anions relative to an all-HB analogue and, impressively,i sf ound to be selective for nitrate over other oxoanions and chloride.…”
mentioning
confidence: 99%
“…Of the relatively few examples of XB anion receptors reported to date, it is noteworthy that all display promising, and significantly contrasting, anion recognition behaviour when compared to HB analogues, by virtue of their comparable bond strengths and more strict linear geometry preference 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42. Importantly in a significant step forward for highlighting the potential importance of halogen bonding in anion supramolecular chemistry, we have recently demonstrated the first examples of solution phase halogen bonding being exploited to control and facilitate the anion‐templated assembly of interlocked structures43, 44, 45, 46, 47 and demonstrated that the incorporation of halogen bond donor atoms into a [2]rotaxane host cavity dramatically improves the anion recognition capabilities of the XB interlocked receptor 48, 49, 50, 51…”
mentioning
confidence: 99%